1986
DOI: 10.1063/1.337385
|View full text |Cite
|
Sign up to set email alerts
|

Infrared study of KTiOPO4 single crystals hydrothermally grown in H2O and D2O solutions

Abstract: A detailed infrared study has identified the spectral features of potassium titanate orthophosphate, KTiOPO4 (KTP), between 4000 and 2200 cm−1. KTP single crystals grown by hydrothermal and flux methods were examined. By using ordinary and heavy water in separate runs to grow KTP crystals hydrothermally, features that depend on the presence of H2O or D2O in the growth process have been distinguished from features that do not. The effect of multiple OH sites in KTP has been linked with crystal quality and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The trends in the activation energies of the different materials are similar to those reported in [12], but the use of bulk ionic conductivity values in the present case yields a more accurate determination of the actual activation energies than the single frequency values previously reported there and by other researchers. [ 19,20] The carrier concentrations, [VK], calculated for high temperature hydrothermal KTP using the activation energy of 0.3 eV are consistent with previously estimated OH-concentrations, in the range of a hundred ppm [17]. The carrier concentrations expected from the nonstoichiometry based on the growth temperatures in hydrothermal materials are much lower, as described above.…”
Section: Proton Effects On Ionic Conductivitysupporting
confidence: 59%
See 1 more Smart Citation
“…The trends in the activation energies of the different materials are similar to those reported in [12], but the use of bulk ionic conductivity values in the present case yields a more accurate determination of the actual activation energies than the single frequency values previously reported there and by other researchers. [ 19,20] The carrier concentrations, [VK], calculated for high temperature hydrothermal KTP using the activation energy of 0.3 eV are consistent with previously estimated OH-concentrations, in the range of a hundred ppm [17]. The carrier concentrations expected from the nonstoichiometry based on the growth temperatures in hydrothermal materials are much lower, as described above.…”
Section: Proton Effects On Ionic Conductivitysupporting
confidence: 59%
“…The total [OH-] in good quality high temperature hydrothermal KTP crystals has previously been estimated to be in the range of a hundred ppm. [17] The OH-distributions in KTP crystals as a function of the growth technique are shown at room temperature and 10 K in [12] and in a Crawford et al (found elsewhere in this proceedings). The distribution of OH-sites in KTP is clearly a function of the growth technique and conditions.…”
Section: Protonsmentioning
confidence: 98%
“…Multiple OH-sites were observed and a correlation of a decrease in doubling efficiency to the presence of multiple OH-sites in room temperature spectra of high temperature hydrothermal material was reported. [20,21] Room temperature infrared spectra obtained in this study ( Figure 2) find that the prominent OH-site associated with the peak at 3566 cm-1 is present in flux and high temperature hydrothermal crystals, but show that this is absent in the low temperature hydrothermal material. The relative [OH-] in the materials examined are not dramatically different.…”
Section: Hydrothermal Crystalsmentioning
confidence: 92%
“…OHincorporation in the crystal could compensate for the formation of VK and increase the [VK] above those present only as a function of the growth temperature, assuming the validity of the temperature dependent VK and VO defect model to hydrothermal materials.The total [OH-] in good quality high temperature hydrothermal material has previously been estimated to be approximately 50-100 ppm. [21] This concentration range would set the [VK] at levels near those calculated for the 950 oC flux grown KTP. The correlation of higher AC conductivity and slightly lower activation energy for conduction to the distribution of OH-sites indicate that specific OH-sites may enhance the mobility of ionic carriers.…”
Section: Hydrogen Effectsmentioning
confidence: 96%
See 1 more Smart Citation